Beverages and sugar-sweetened beverages consumption pattern and amount among adolescents using beverage frequency questionnaire: cross-sectional study - Tahrir M. Aldhirgham; Hanan A. Alfawaz; Nasser M. Al-Daghri (BMC Public Health)
Abstract Background Over 390 million children and adolescents are affected by overweight and obesity worldwide. Similarly, obesity rates are rising in these age groups in the Middle East and Gulf region including Saudi Arabia. Dietary habits are fundamental in childhood overweight and obesity management. Adolescents consume a higher energy intake from free sugars than any other age group, with beverages becoming a significant source of those sugars. Adolescent beverage consumption has been assessed in various populations. However, limited studies have assessed beverage consumption patterns and amounts among adolescents in the Middle East and the Gulf region. This study used beverage frequency questionnaires to assess adolescents’ total beverage consumption(TBC) and sugar-sweetened beverages(SSBs) consumption patterns and amounts. Also, it estimated their contribution to the total energy and nutrient intake and explored the association between consumption and demographic factors, specific obesity parameters, and body composition components. Methods A cross-sectional study was conducted among 15-19years males and females in January and February 2023. Participants(n = 316) were recruited in Riyadh city using a multistage clustered stratified random sampling technique based on region and gender. Participants completed a modified version of the beverage frequency questionnaire. Additionally, anthropometric measurements and body composition were measured. Results Participants had a similar TBC(median = 1702 ml/day), but males and females differed in their consumption frequency of various beverage types(7 out of 25). SSB consumption(median = 478 ml/day) accounted for 28% of TBC and 100% and 75% of sugar and carbohydrates from TBC, respectively. BMI/age groups showed similar beverage consumption frequencies in almost all types(24 out of 25). A significant association was found between SSB intake and grade in male participants. The correlation between TBC, SSB consumption, and obesity parameters/body composition components was overall weak(r ≤ 0.5). Conclusions Beverage consumption amounts may not have a potential risk independently among older adolescents. However, beverage consumption habits and quality may vary based on gender and other socio-demographic factors. Highlighting the need for dietary habits, diet quality assessment and improvement in adolescents, and targeted public health interventions. Further research may investigate beverage consumption among younger adolescents, include broader regional comparisons, and explore additional impact factors such as taxation and advertising.